2011
DOI: 10.1631/jzus.b1000385
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged hypervolemic hemodilution decreases functional capillary density of ileal mucosa in pigs revealed by sidestream dark-field imaging

Abstract: Prolonged HHD established by crystalloid solution significantly decreased ileal villus FCD when compared to restrictive fluid regimen. An inappropriate degree of HHD can be harmful during uncomplicated abdominal surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…Our main findings were the (i) feasibility of a follow-up assessment of microcirculation using Cytocam-IDF in a post-cardiac surgery ward and (ii) the increase in the FCD during the follow-up in post-ICU cardiac surgery patients undergoing diuretic therapy. Although several studies have shown that fluid administration decreases FCD (Atasever et al 2011 , 2012 ; Turek et al 2011 ; Yuruk et al 2012 ), this is, to our knowledge, the first study demonstrating the conceivable beneficial effect of fluid de-escalation in recruiting microcirculation by increasing the FCD.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…Our main findings were the (i) feasibility of a follow-up assessment of microcirculation using Cytocam-IDF in a post-cardiac surgery ward and (ii) the increase in the FCD during the follow-up in post-ICU cardiac surgery patients undergoing diuretic therapy. Although several studies have shown that fluid administration decreases FCD (Atasever et al 2011 , 2012 ; Turek et al 2011 ; Yuruk et al 2012 ), this is, to our knowledge, the first study demonstrating the conceivable beneficial effect of fluid de-escalation in recruiting microcirculation by increasing the FCD.…”
Section: Discussionmentioning
confidence: 60%
“…Maintenance of adequate FCD is important for organ perfusion and function (Groner et al 1999 ; Tsai et al 1995 ). Several animal and human studies have reported that hemodilution decreases the FCD (Atasever et al 2012 ; Ferrara et al 2016 ; Turek et al 2011 ). Atasever et al demonstrated a decrease in the FCD in the sublingual microcirculation as an effect of the priming solution causing hemodilution during on-pump cardiac surgery (Atasever et al 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…; Turek et al. ). Unlike the neonatal skin, the skin of the adult is too thick to reliably view the subcutaneous circulation, but videomicroscopy has been used for both structural and functional assessment of dermal loops for comparisons of functional capillary density (FCD) between different groups (Treu et al.…”
Section: Discussionmentioning
confidence: 98%
“…LDF appears to be the most reliable method for monitoring the microcirculation in the large bowel or rectum. Other methods include sidestream dark field imaging, which is based on orthogonal polarization spectral imaging, and intestinal microdialysis [5][6][7][8][9]. Larger studies, as well as comparisons of individual methods in larger samples, have yet to be conducted.…”
Section: Discussionmentioning
confidence: 99%